S. Industrial Clusters in Al-Hassan Industrial Estate Study in Economic Geography: Industrial Clusters in Al-Hassan Industrial Estate - sababhi, safa (Advances in Social Sciences Research Journal, 2020)
The industrial estates represent the most prominent forms of support provided by the state to the industrial sector by achieving external savings that support the establishment and continuation of industries. The successive Jordanian governments seek to support the industrial sector and provide it with all forms of incentives in order to improve the growth of the Jordanian economy and providing job opportunities. Therefore, they established (6) industrial estates distributed all over the Kingdom’s governorates. However, these industrial clusters are still working within the classic classical conception of clustering, as a place for grouping industries, and were unable to switch to the concept of industrial clusters resulting from interaction and integration between industries, while the industrial clusters turned to be a development strategy leading to the growth and development of industries. So, this study aimed to find out if the industries in the Industrial City of Al-Hassan Industrial Estate managed to shift from the traditional concept of clustering to the concept of cluster, and to know the reasons preventing this transformation. The study adopted the descriptive analytical approach and the qualitative analysis of the data collected through the study tool (the questionnaire). The study concluded that the industries in Al-Hassan Industrial Estate were unable to transform into a cluster based on interaction and exchange, and the interaction between factories and the local community represented by academic institutions is at its lowest levels. Therefore, the study recommends restructuring the industrial estates and technology areas in the Kingdom to shift from the traditional role of the industrial cluster to the modern concept.